Heterologous cAd3-Ebola and MVA-EbolaZ vaccines are safe and immunogenic in US and Uganda phase 1/1b trials - Myra Happe; Amelia R. Hofstetter; Jing Wang; Galina V. Yamshchikov; LaSonji A. Holman; Laura Novik; Larisa Strom; Francis Kiweewa; Salim Wakabi; Monica Millard; Colleen F. Kelley; Sarah Kabbani; et al. (npj Vaccines, 2024)
Abstract Ebola virus disease (EVD) is a filoviral infection caused by virus species of the Ebolavirus genus including Zaire ebolavirus (EBOV) and Sudan ebolavirus (SUDV). We investigated the safety and immunogenicity of a heterologous prime-boost regimen involving a chimpanzee adenovirus 3 vectored Ebola vaccine [either monovalent (cAd3-EBOZ) or bivalent (cAd3-EBO)] prime followed by a recombinant modified vaccinia virus Ankara EBOV vaccine (MVA-EbolaZ) boost in two phase 1/1b randomized open-label clinical trials in healthy adults in the United States (US) and Uganda (UG). Trial US (NCT02408913) enrolled 140 participants, including 26 EVD vaccine-naïve and 114 cAd3-Ebola-experienced participants (April-November 2015). Trial UG (NCT02354404) enrolled 90 participants, including 60 EVD vaccine-naïve and 30 DNA Ebola vaccine-experienced participants (February-April 2015). All tested vaccines and regimens were safe and well tolerated with no serious adverse events reported related to study products. Solicited local and systemic reactogenicity was mostly mild to moderate in severity. The heterologous prime-boost regimen was immunogenic, including induction of durable antibody responses which peaked as early as two weeks and persisted up to one year after each vaccination. Different prime-boost intervals impacted the magnitude of humoral and cellular immune responses. The results from these studies demonstrate promising implications for use of these vaccines in both prophylactic and outbreak settings.